Innovations in rural and agricultural finance: Rural leasing: An alternative to loans in financing income-producing assets - Nair, Ajai (International Food Policy Research Institute, 2010)
Credit for investments that pay back in the medium to long term (three to five years or longer) is in short supply in rural areas. Credit unions and microfinance institutions (MFIs), which generally have better outreach than commercial banks in rural areas, typically provide only short-term credit. Credit available from informal sources (such as moneylenders, family, and friends) is usually both short term and too costly for investment financing. For rural enterprises seeking to acquire equipment-a typical investment need-to modernize production and thereby increase productivity, one solution may be financial leasing.